Breastfed infants' exposure to polychlorinated biphenyls, polychlorinated dibenzo-p-dioxins and dibenzofurans, and per- and polyfluoroalkyl substances: A cross-sectional study of a municipal waste incinerator in China. (December 2022) - Xu, Peiwei; Zheng, Yibin; Wang, Xiaofeng; Shen, Haitao; Wu, Lizhi; Chen, Yuan; Xu, Dandan; Xiang, Jie; Cheng, Ping; Chen, Zhijian; Lou, Xiaoming
Abstract: A municipal waste incinerator (MWI) in Zhejiang, China, operating since 2008 was completely reconstructed from 2016 to 2019. In 2013, we conducted a cross-sectional study of breastfeeding mothers living near the MWI. We evaluated the concentrations of polychlorinated biphenyls (PCBs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in the mothers' breast milk and their infants' estimated daily intake (EDI). To investigate the temporal variations of these pollutants, we conducted a cross-sectional study of 29 mothers in 2019. We assessed the levels of 18 PCB congeners, 17 PCDD/F congeners, and 21 per- and polyfluoroalkyl substance (PFAS) congeners in breast milk and estimated the EDI. The mean total concentrations of PCDD/Fs (ΣPCDD/Fs) and PCBs (ΣPCBs) were 81.2 and 4.90 ng/g lipid, respectively, while the toxic equivalent quantity (TEQ) levels of ΣPCDD/Fs and dioxin-like PCBs (ΣDL-PCBs) were 2.7 and 1.4 pg WHO-TEQ/g lipid, respectively. Compared to our 2013 measurements, the mass concentrations of ΣPCDD/Fs and ΣPCBs decreased by 13% and 35%, respectively (3.361 vs. 2.915 pg/g wet weight [ww] and 269.1 vs. 175.0 pg/g ww, respectively). The TEQ-ΣPCDD/F levels decreased by 67% (0.241 vs. 0.080 pg/g ww), but the TEQ-ΣDL-PCB levels increased by 11% (0.046 vs. 0.051 pg WHO-TEQ/g ww). The median concentration of PFASs was 0.250 ng/mL, ranging from 0.151 to 0.833 ng/mL. The infants' mean EDI of total PCDD/Fs and DL-PCBs was 17.7 pg TEQ/kg body weight [bw], representing a 20% decline compared to 2013. The average EDI levels of PFOS, PFOA, and PFNA were 5.8, 17.9, and 1.7 ng/kg bw, respectively. A comprehensive comparison of the results with studies from around the world showed that the potential health risks posed by legacy PCDD/F and PCB pollutants were not as grave for mothers and infants living near this MWI, but the emerging PFAS pollutants represented a new cause for concern. Main findings: The potential health risks posed by legacy PCDD/F and PCB pollutants were not particularly serious for mothers and infants living near the MWI, but the emerging PFAS pollutants raised new concerns. Graphical abstract: Median levels of PFASs (ng/L) in breast milk worldwide over the past two decades. Image 1 Highlights: The body burdens of PCDD/Fs and PCBs decreased markedly compared to 2013. The infants' EDI declined 20% compared to the 2013 measurements. The TEQ levels of total DL-PCBs and PCDD/Fs were considerably lower. High body burdens of total PFASs were found in this study.